Administrative-Legal Regulation of the Implementation of Risk-Oriented Access in the Security Sector of Ukraine - Buhaichuk, K. L. (Вісник Харківського національного університету внутрішніх справ, 2025)
The publication provides a scientific analysis of the concept and characteristics of the category of “risk”, as well as the procedure for applying the concept of “risk management” in the activities of state authorities that are part of the system of subjects of the security and defense sector of Ukraine. An analysis of the state of administrative and legal regulation of issues related to the implementation of risk-oriented approaches in the activities of the Ministry of Defense of Ukraine, the Ministry of Internal Affairs of Ukraine and other subjects of the security and defense sector is carried out. It is emphasized that the content of the risk-oriented approach in the activities of security and defense subjects can be considered from two positions. In the first case, it is related to increasing the efficiency of internal management processes in the relevant state body, and in the second – it is related to the sphere of public relations, where the mentioned subjects exercise their security and law enforcement powers, which are defined by the current legislation of Ukraine. The author’s understanding of the risk-oriented approach in the activities of security and defense sector entities is proposed as the implementation of regulatory and regulated procedures for managing risks that arise during the intra-organizational activities of relevant state bodies, as well as during the exercise of their powers enshrined in law to protect the rights and legitimate interests of individuals and citizens, ensure the sovereignty, independence and territorial integrity of the state, national security, and combat crime and other offenses. The need to develop and adopt a framework order (methodology) to determine the standard procedure for applying a risk-oriented approach in the activities of security and defense sector entities both in the field of their intra-organizational activities and in the field of their subject competence, covering issues of ensuring the territorial integrity and protection of the state, ensuring national security, combating offenses, ensuring public order and safety, is substantiated.